Penyakit Bukan Utama Tanaman Gandum di Kabupaten Timor Tengah Utara - Aloysius Rusae (Fakultas Pertanian, Universitas Timor, 2018)
Wheat (Triticum spp.) Is a cereal plant, has a fairly high nutrient content. The area of North Central Timor has prospects for wheat development. The existence of pathogens in wheat crops has not been observed and identified because there has never been any wheat cultivation in the area. The purpose of this study is to know other diseases that attack wheat crops when introduced to North Central Timor District, East Nusa Tenggara Province. The methods used were wheat cultivation, disease observation, and non-primary disease identification. Varieties of grain grown are varieties of Dewata, Selayar, and Nias. Observation of the incidence and severity of disease performed every 4 weeks. Identification of pathogens is done by morphological characterization with the help of identification keys. Laboratory research for disease identification was done in Plant Micropology Laboratory, Department of Plant Protection, Bogor Agricultural University. Other diseases that infect wheat crops are Fusarium shoots, leaf spot, Curvularia and Helminthosporium hulls, and twisted leaves. The percentage of incidence of all four diseases is very low.